In vitro and in vivo screening of native lactic acid bacteria toward their selection as a probiotic in broiler chickens - Blajman, Jesica E.; Gaziano, Cristian; Zbrun, María Virginia; Soto, Lorena Paola; Astesana, Diego Martín; Berisvil, Ayelén Patricia; Romero Scharpen, Analía; Signorini, Marcelo; Frizzo, Laureano Sebastian (2018)
Among 360 isolates from the gastrointestinal tract (GIT) of broilers, eleven isolates which showed in vitro probiotic properties were identified and selected for further tests. After the in vitro screening, three strains were chosen for the in vivo study of persistence of fresh cultures and then one strain was selected for the in vivo study of persistence of lyophilized culture. Lyophilized Lactobacillus salivarius DSPV 001P was capable of persisting in broilers during a complete rearing, even 28 days following cessation of administration. L. salivarius DSPV 001P administered to broilers and recovered from GIT was compared by pulsed-field gel electrophoresis (PFGE) to ensure that the same genotype was persistently identified. A combination of in vitro and in vivo screening of native lactic acid bacteria (LAB) described in this study may offer a method for selecting the most suitable strain for potential application as a broiler probiotic supplement.